Diagnostic value of coronary CT angiography in comparison with invasive coronary angiography and intravascular ultrasound in patients with intermediate coronary artery stenosis: results from the prospective multicentre FIGURE-OUT (Functional Imaging criteria for GUiding REview of invasive coronary angiOgraphy, intravascular Ultrasound, and coronary computed Tomographic angiography) study - Doh, Joon-Hyung (Oxford University Press, 2014)
AIMS: The anatomical criteria for the diagnosis of ischaemia referenced by fractional flow reserve (FFR) from non-invasive coronary computed tomographic angiography (CCTA), invasive coronary angiography (ICA), and intravascular ultrasound (IVUS) have not been evaluated contemporarily in a large-scale study. The aim of this study was to assess the diagnostic value of CCTA compared with ICA and IVUS in patients with intermediate coronary stenosis. METHODS AND RESULTS: CCTA, ICA, IVUS, and FFR were performed in 181 coronary lesions with intermediate severity. Minimal lumen diameter (MLD) and per cent diameter stenosis (%DS) were determined by CCTA and ICA, whereas minimal lumen area (MLA) was determined by CCTA and IVUS. Inducible ischaemia was defined by FFR ≤0.80. Diagnostic performances from non-invasive and invasive methods were compared. FFR ≤0.80 was observed in 49 (27.1%) lesions. CCTA MLD was smaller than ICA MLD (1.3 ± 0.5 vs. 1.5 ± 0.4 mm, P < 0.001), CCTA %DS was higher than ICA %DS (54.0 ± 14.0 vs. 50.3 ± 12.8%, P < 0.001), and CCTA MLA was smaller than IVUS MLA (2.2 ± 1.2 vs. 3.2 ± 1.2 mm(2), P < 0.001). This trend was consistent irrespective of lesion location, lesion severity, and plaque characteristics. For the determination of ischaemia, diagnostic performance of CCTA %DS was lower than ICA %DS [area under the curve (AUC) 0.657 vs. 0.765, P = 0.04], and that of CCTA MLA was lower than IVUS MLA (AUC 0.712 vs. 0.801, P = 0.03). CONCLUSION: Anatomical criteria for the diagnosis of ischaemia-producing coronary stenosis differ by non-invasive and invasive methods. Compared with invasive methods, CCTA presents overestimation in assessing lesion severity and lower diagnostic performance in assessing ischaemia.